2012
DOI: 10.1089/gtmb.2012.0024
|View full text |Cite
|
Sign up to set email alerts
|

Partial Microdeletions in the Y-Chromosome AZFc Region Are Not a Significant Risk Factor for Spermatogenic Impairment in Tunisian Infertile Men

Abstract: Azoospermia factor (AZF) subdeletions were reported to be significant risk factors for spermatogenesis. In this study, we screened classical and partial microdeletions of the Y-chromosome AZF region in a group of 261 infertile men. Partial deletions were also screened in a control group of fertile men (n=124). In addition, Y haplogroups were analyzed in 24 gr/gr deleted patients. Among the 261 studied infertile men, seven subjects were found to have classical microdeletions. The most common partial deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Using the Y chromosome microdeletion in infertile Tunisian men 6 STSs markers, Hadj-Kacem et al [19] have reported an overall of 16% of Y chromosome microdeletions in 163 infertile Tunisian men with normal karyotype subdivided into 3 groups: azoospermic, oligozoospermic (less than 20 × 10 6 spz/mL), and normozoospermic men (more than 20 × 10 6 spz/mL). With the same STSs markers, two studies performed by Ghorbel et al have detected a lower frequency in azoospermic and oligozoospermic groups: 1.3% [6] and 2.7% [20], but chromosomal abnormalities in these reports were included in the first study and unspecified in the latter one ( [22]. In the present study, 2/74 azoospermic men (2.7%) showed Y chromosome microdeletions.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Using the Y chromosome microdeletion in infertile Tunisian men 6 STSs markers, Hadj-Kacem et al [19] have reported an overall of 16% of Y chromosome microdeletions in 163 infertile Tunisian men with normal karyotype subdivided into 3 groups: azoospermic, oligozoospermic (less than 20 × 10 6 spz/mL), and normozoospermic men (more than 20 × 10 6 spz/mL). With the same STSs markers, two studies performed by Ghorbel et al have detected a lower frequency in azoospermic and oligozoospermic groups: 1.3% [6] and 2.7% [20], but chromosomal abnormalities in these reports were included in the first study and unspecified in the latter one ( [22]. In the present study, 2/74 azoospermic men (2.7%) showed Y chromosome microdeletions.…”
Section: Resultssupporting
confidence: 48%
“…Differences in the methods applied for the Yq microdeletion screening in Tunisian studies might account for varying deletion frequencies. The choice and number of STS markers differed widely, ranging from 6[6,19,20] to 20 STS[21] despite the fact that Simoni et al showed that the detection rate did not depend on the number and choice of markers used…”
mentioning
confidence: 99%
“…In addition, several studies have investigated whether the b2/b3 or b1/b3 subdeletions are associated with spermatogenic failure. However, they also have produced mixed results [16][17][18][19][20][21][22]. Therefore, the present results may be reasonable.…”
Section: Discussionsupporting
confidence: 48%
“…The b1/b3 and b2/b3 subdeletions are also associated with male infertility [16][17][18][19]. However, several studies could not link these subdeletions to male infertility [15,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…While in some studies the frequency of AZFc subdeletions (mainly the gr/gr) is higher in infertile men as compared to fertile controls [5,11,[20][21][22]; others have failed to confirm this association [23,24]. Based on four meta-analysis studies and a large population study involving >20,000 individuals it appears that the gr/gr deletion is a risk factor for male infertility [13,20,21,25,26]; the odds ratio is estimated to be 1.4-2.4 [5,20,21,25,26].…”
Section: Introductionmentioning
confidence: 99%